THE DIAGRAM OF MOODS: THEORY AND REALITY - Semen Yu. Bogatyrev (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The article studies the issue of identifying business market value in deals on merges and acquisitions, which is connected with identifying the discount rate by using the method of cash flows discounting. During the post-crisis period after 2009 not only Russian value analysts but also overseas ones have been facing this problem. Only now we can observe a sharp increase in the Federal Reserve System rate, though not long ago valuers did not know how to build the discount rate with the negative figures of the interest rate in Europe and its minimum figures in the US. This research investigates the problem from the point of view of behavioral finance. Crisis and prosperous years are analyzed in view of the emotional background, which gives a certain line in shaping the mood of M & A market participants. To solve the problem value assessment was carried out by the method of cash flow discounting of a great number of Russian banks put up for sale and later quantitative methods of finance decision-making were applied for processing numerous findings. The novelty of obtained findings is connected with the fact that today methods of behavioral research are not used in finance practice and in scientific developments in Russia. They are rather limited abroad. Theoretical works, which formed the foundation for the empiric research, were used earlier by foreign scientists at the stock exchange. Such research is a pioneer on the Russian M & A market.